Polymyxin B Agonist Capture Therapy for Intrauterine Inflammation: Proof-of-Principle in a Fetal Ovine Model. (May 2014) - Saito, Masatoshi; Payne, Matthew S.; Miura, Yuichiro; Ireland, Demelza J.; Stock, Sarah; Kallapur, Suhas G.; Kannan, Paranthaman S.; Newnham, John P.; Kramer, Boris W.; Jobe, Alan H.; Keelan, Jeffrey A.; Kemp, Matthew W.
Intrauterine infection is a leading cause of preterm birth (PTB), most notably in deliveries occurring before 32 weeks gestation. Preterm infants exposed to intrauterine inflammation are more likely to have a host of neurological, respiratory, gastrointestinal, and visual pathologies. Preventing preterm delivery and protecting the fetus from injury is thus likely to require treatment of both intrauterine infection and inflammation. Polymyxin B (PMXB) is a cationic peptide antibiotic that binds Escherichia coli lipopolysaccharides (LPS) and prevents inflammatory activation. We hypothesized that intraamniotic administration of PMXB would selectively inhibit LPS-driven inflammation, serving as a proof-of-principle for targeted agonist capture therapy as a treatment for PTB and fetal injury. In vitro studies with primary fetal ovine keratinocytes demonstrated a significant and sustained reduction in tumor necrosis factor α and interleukin 8 messenger RNA expression after treatment with PMXB and LPS, relative to cells treated with LPS alone. In vivo studies with fetal sheep demonstrated a significant reduction in proinflammatory cytokines in the amniotic fluid and fetal lung (but not fetal skin or chorioamnion) in LPS + PMXB-treated animals, relative to those treated with LPS alone. These data are consistent with a partial resolution of LPS-driven intrauterine inflammation. They suggest the potential for agonist capture as a conceptual means of resolving the proparturition inflammation caused by infection of the amniotic cavity.